Criterion is a touchstone in study of early angiosperms - Xin Wang (Open Journal of Plant Science - Peertechz Publications, 2021)
Herendeen et al. set up a criterion identifying fossil angiosperms while they named five examples of fossil angiosperms in the same paper. Their normal-appearing operation, however, is fundamentally flawed: their exemplar fossil angiosperms did not honor their own criterion. This operation confused their proponents as well as other botanical researchers, hindering healthy progress in study on the origin of angiosperms. Herendeen et al. are obligated to give a plausible explanation for their perplexing operation.  *Nature Plants has been informed of the problem in Herendeen et al. (2017). Nature Plants has refused to fix the problem due to reasons, according to the communication with Dr. Chris Surridge, an editor of Nature Plants.